The boyfriend candidate [large type] - Winstead, Ashley (Center Point Large Print, 2023)
"As a shy school librarian, Alexis Stone is comfortable keeping out of the spotlight. But when she's dumped for being too meek -- in bed! -- she decides she needs to change. And what better way to kick-start her new, more adventurous life than with her first one-night stand? Enter Logan, the gorgeous, foul-mouthed stranger she meets at a hotel bar. Audacious and filterless, Logan is Alexis's opposite -- and boy, do opposites attract! Just as she's about to fulfill her hookup wish, the hotel catches fire in a freak lightning storm. In their rush to escape, Logan is discovered carrying her into the street, where people are waiting with cameras. Cameras Logan promptly -- and shockingly -- flees. Alexis is bewildered until suddenly pictures of her and Logan escaping the fire are all over the internet. Turns out Logan is none other than Logan Arthur, the hotshot candidate challenging the Texas governor's seat. The salacious scandal is poised to sink his career -- and jeopardize Alexis's job -- until a solution is proposed: he and Alexis could pretend to be in a relationship until election day . . . in two months. What could possibly go wrong?"--